Strategi Guru Pendidikan Agama Islam dalam Menanggulangi Kenakalan Siswa di MA Al Wathoniyah 5 - Mulvi Siroj; Heru Wibowo (Journal on Education, 2024)
This study reviews the approaches applied by Islamic education teachers in addressing the issue of juvenile delinquency among students at MA Al Wathoniyah 5, East Jakarta. The primary aim of this research is to identify the methods employed by Islamic education teachers in responding to juvenile delinquency and to explore the elements that support or hinder teachers in managing delinquency issues among teenage students at MA Al Wathoniyah 5. The research presented is qualitative. The research location is at MA Al Wathoniyah 5, located at Jl. I Gusti Ngurah Rai, Buaran 1, RT. 016/RW. 008, RT.16/RW.8, Jatinegara, Cakung District, East Jakarta City, which the researcher chose as the target. In collecting data for this study, three methods were used: first, the Observation method was employed to monitor the delinquent behaviour of students at the MA; second, the Interview method was applied to Islamic Education Teachers, Counseling Teachers, and the Vice Principal of Student Affairs to obtain confirmation regarding the strategies used in addressing the issue of juvenile delinquency at MA Al Wathoniyah 5; and third, the Documentation method. The research indicates that Islamic Education Teachers implement several strategies in handling deviant behaviour or juvenile delinquency at MA Al Wathoniyah 5. The methods used include preventive strategies for prevention, curative strategies for remediation, and approaches through direct learning. However, some cases of deviant student behaviour have not been fully resolved.